Gendered late working life trajectories, family history and welfare regimes: evidence from SHARELIFE - Schmitz, Wiebke [Verfasser]; Naegele, Laura [Verfasser]; Frerichs, Frerich [Verfasser]; Ellwardt, Lea [Verfasser] (My University, 2023)
“Earlier employment choices based on family events in earlier life have an impact up until late working life, especially in welfare regimes that encourage the breadwinner-caretaker division. We investigate types of late employment patterns and how these are associated with earlier family events. We also test whether the association between early family history and late working life varies across five welfare regimes. Using retrospective life history data from SHARELIFE, our sample consists of 10,913 women and 10,614 men aged 65 years and older. Late working life trajectories are analyzed using gender separate sequence analyses, which are summarized into eight groups applying cluster analyses. Using average marginal and interaction effects, we explain how the association between types of late working life, coresidential partnership history and parenthood history differs by welfare states. For instance, women’s late employment is either shaped by unpaid care or paid (full- or part-time) work but not both, whereas men’s late working life is mainly shaped by full-time work. Family history in earlier life is linked to unpaid care and part-time work—an association strongest in liberal and southern welfare regimes. However, among men earlier family events are linked to full-time work. Policymakers need gender-specific strategies to integrate workers into late working life. The implementation of new policies should aim to prevent these social inequalities in early life, as employment decisions caused by family history in earlier life stages - especially for women - tend to cumulate over the life course.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 2.4.5 Gender Mainstreaming; P 1.3 Frauen; 370; 300; Berufswahl; Bildungsentscheidung; Berufsentscheidung; Berufsverlauf; Einflussfaktor; Geschlechterrolle; Familienstruktur; Erwerbsverhalten; Familienarbeit